2014
DOI: 10.1016/j.ygeno.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatics approach to reanalyze the genome annotation of kinetoplastid protozoan parasite Leishmania donovani

Abstract: Leishmania donovani is a kinetoplastid protozoan parasite which causes the fatal disease visceral leishmaniasis in humans. Genome sequencing of L. donovani revealed information about the arrangement of genes and genome architecture. After curation of the genome sequence, many genes in L. donovani were assigned as truncated or "partial" genes by the genome sequencing group. In the present study, we have carried out an extensive analysis and attempted to improve the gene models of these partial genes. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…donovani assemblies published to date. This new assembly represents an improved genome regarding the current reference genome (BPK strain 67 ), which is incomplete and presents some annotation deficiencies 75 . Thus, apart from eliminating the gaps, the genome size has been extended about 1.8 Mb in length and the total number of annotated genes has been increased by 400 genes, regarding the current reference L .…”
Section: Resultsmentioning
confidence: 99%
“…donovani assemblies published to date. This new assembly represents an improved genome regarding the current reference genome (BPK strain 67 ), which is incomplete and presents some annotation deficiencies 75 . Thus, apart from eliminating the gaps, the genome size has been extended about 1.8 Mb in length and the total number of annotated genes has been increased by 400 genes, regarding the current reference L .…”
Section: Resultsmentioning
confidence: 99%
“…One new aspect of this work is the discovery of chromosomal translocations which have not been observed before in old world Leishmania species [ 70 72 ]. Studies in yeast have also indicated an increase of translocations events and chromosomal rearrangements when either MRE11 or RAD50 are mutated [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding led to the use of L. major (Friedlin) genome as a template to facilitate the assembly process of most of the Leishmania genomes reported afterwards. However, as demonstrated in this and other works 32 , that approach may lead to introduce assembly errors that would compromise future studies regarding gene content, gene models and genome architecture. Here, we present a de novo assembly of the L. infantum (JPCM5) genome based on sequence data derived from both long (PacBio) and short (Illumina) reads that yielded the expected 36 chromosomal-size contigs, without discontinuities and undetermined sequence (Ns), which are abundant in the current genome (GeneDB.org).…”
Section: Resultsmentioning
confidence: 89%